MODEL OF MUALLAF DEVELOPMENT BASED ON LOCAL WISDOM IN MUSLIM MINORITY VILLAGES: A CASE STUDY OF NGADAS VILLAGE, EAST JAVA - Jefri Mardiansyah A; Ishomuddin; Romelah; Muh. Zakki Amrulloh (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research examines a model of muallaf development based on local wisdom within a Muslim minority community, with a case study in Ngadas Village, Poncokusumo District, Malang Regency. This village has a unique socio-religious character, where Muslims are a minority group, mostly increasing through conversion due to marriage and social interaction. This condition necessitates a development pattern that is not only doctrinal but also adaptive to local culture and interreligious relations. This research uses a qualitative approach with a case study design. Data was collected through participant observation, in-depth interviews, and documentation, and analyzed interactively through condensation, presentation, and conclusion drawing with data triangulation. The results show that muallaf development is carried out through a non-directive community-based model that integrates local wisdom into socio-religious traditions, such as tahlilan, Friday prayers, and daily interactions. This model contributes to strengthening the Islamic identity of muallaf and maintaining social harmony, although it still faces limitations in resources and development planning.